2020
DOI: 10.1063/1.5143018
|View full text |Cite
|
Sign up to set email alerts
|

Bound states and the potential parameter spectrum

Abstract: In this article, we answer the following question: If the wave equation possesses bound states but it is exactly solvable for only a single non-zero energy, can we find all bound state solutions (energy spectrum and associated wavefunctions)? To answer this question, we use the "tridiagonal representation approach" to solve the wave equation at the given energy by expanding the wavefunction in a series of energy-dependent square integrable basis functions in configuration space. The expansion coefficients sati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The potential parameter spectrum (PPS) is a non traditional numerical eigenvalue method that originated in the context of the TRA whenever the basis set is energy dependent 11 . This happens, for example, when the TRA constraints dictate that one or more of the basis parameters is/are energy dependent.…”
Section: Potential Parameter Spectrummentioning
confidence: 99%
See 1 more Smart Citation

Deformed Morse-like potential

Assi,
Alhaidari,
Bahlouli
2021
Preprint
Self Cite
“…The potential parameter spectrum (PPS) is a non traditional numerical eigenvalue method that originated in the context of the TRA whenever the basis set is energy dependent 11 . This happens, for example, when the TRA constraints dictate that one or more of the basis parameters is/are energy dependent.…”
Section: Potential Parameter Spectrummentioning
confidence: 99%
“…In section III we present the theoretical derivation of the solvable potential (1) using the tridiagonal representation approach. In section IV we compute the energy spectrum associated with this potential using the potential parameter spectrum (PPS), 11 which is a highly non traditional eigenvalue problem. In section IV we confirm the validity of our generated energy spectrum using a direct numerical diagonalization technique in a suitable L 2 basis, 12 and the asymptotic iteration method.…”
Section: Introductionmentioning
confidence: 99%

Deformed Morse-like potential

Assi,
Alhaidari,
Bahlouli
2021
Preprint
Self Cite
“…Summarizing: We have shown that the application of the TRA PPS to the Kratzer-Fues potential [1] has a serious flaw with regard to the values of the radial quantum number k. The resulting expression for the spectrum does not appear to be correct. In addition to it, the well known Frobenius method [2], which resembles the TRA PPS and is taught in undergraduate courses on quantum mechanics and quantum chemistry [6], is far simpler, clearer and more elegant.…”
mentioning
confidence: 96%